MUSIC LISTENING AS MUSICKING AND STRONG MUSICAL EXPERIENCE - Paipare, Mirdza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Research about musical experience can be found in various works written about the experience of joy felt from music listening or seeing visual art. Gabrielsson and Lindström gathered and analysed more than 1000 case descriptions over a period of ten years, in which participants were asked to describe in as much detail as possible the most powerful and most impressive musical experiences they had ever had. References to such musical experiences in literature are not rare, however they are related to a variety of results – involving demographics, geography, environment, etc. The author conducted a phenomenological analysis as a subjective psychological aspect’s research method of musical experience, where music listening and musical experience ‘goes together’ with musicking.